Reduced residual cholesterol is associated with increased mortality risk in patients with aneurysmal subarachnoid Hemorrhage: a retrospective study - Zeng, Xihang; Wang, Ruoran; Xu, Jianguo (Frontiers in Neurology, 2025)
BackgroundResidual cholesterol has been confirmed to be associated with the incidence of stroke and its prognosis. However, there is no study exploring the relationship between residual cholesterol and mortality in cases of aneurysmal subarachnoid hemorrhage (aSAH). Therefore, this study investigated the association between residual cholesterol levels and aSAH mortality.MethodsA restricted cubic spline was used to show the relationship between residual cholesterol and mortality risk associated with aSAH. Univariate and multivariate logistic regression models were employed to identify independent risk factors for mortality. The independent risk factors identified in the multivariate logistic regression were combined to develop a predictive model for mortality risk. The receiver operating characteristic curve (ROC) was used to evaluate the predictive value of residual cholesterol and the developed predictive model.ResultsAmong the aSAH patients included in the study, 20.0% experienced 30-day mortality. There were no significant differences in total cholesterol (p = 0.121), low-density lipoprotein cholesterol (p = 0.143), and triglycerides (p = 0.254) between survivors and non-survivors; however, high-density lipoprotein cholesterol (p = 0.021) was higher in non-survivors. Residual cholesterol (p < 0.001) was significantly lower among non-survivors. Multivariate logistic regression analysis revealed seven significant risk factors related to the mortality of aSAH including the Glasgow Coma Scale (GCS) (p < 0.001), modified Fisher Scale (mFisher) (p = 0.032), white blood cell count (p = 0.004), glucose levels (p = 0.008), residual cholesterol (p = 0.047), delayed cerebral ischemia (p < 0.001), and surgical options (p < 0.001). A predictive model for aSAH mortality was developed by combining these seven significant factors. The area under the ROC (AUC) for this predictive model was 0.911, while the AUC for residual cholesterol was 0.603.ConclusionResidual cholesterol is negatively associated with mortality risk in aSAH. Evaluating residual cholesterol is helpful in risk stratification of aSAH patients.